Teacher Strategy to Help Second Grade Students with Early Reading Difficulties - Mohamad Zubad Nurul Yaqin; Fazat Arifatul Ulfah (Jurnal Ilmiah Sekolah Dasar, 2023)
Reading difficulties are a common problem faced by early grade elementary school students who have learning difficulties. Students' reading difficulties will have an impact on low student learning outcomes and will have an impact on students' acquisition of knowledge at the next level. The aims of this study is to analyze teacher’s strategy to overcome students early reading difficulties. This research is a descriptive qualitative research. The subjects of this study were 1 school principal, 2 teachers, and 16 grade II elementary school students. Data collection techniques using interview techniques, observation, and documentation. Data analysis was carried out by reducing data, presenting data and drawing conclusions. The results of this study are the strategies used by teachers comprises of differentiated instructions, assessments to determine the next suited treatment based on students’ needs, and the use of learning media based on students’ level of reading skill. It can be concluded that the teachers as someone who is responsible for their students must be aware of their needs and best suited strategies that met students’ needs.